CD8+CD161+ T-Cells: Cytotoxic Memory Cells With High Therapeutic Potential - Konduri, Vanaja; Oyewole-Said, Damilola; Vazquez-Perez, Jonathan; Weldon, Scott A.; Halpert, Matthew M.; Levitt, Jonathan M.; Decker, William K. (Frontiers in Immunology, 2021)
NK1.1 and its human homolog CD161 are expressed on NK cells, subsets of CD4+ and CD8+ T cells, and NKT cells. While the expression of NK1.1 is thought to be inhibitory to NK cell function, it is reported to play both costimulatory and coinhibitory roles in T-cells. CD161 has been extensively studied and characterized on subsets of T-cells that are CD1d restricted, IL-17 producing CD4+ (TH17 MAIT cells) and CD8+ T cells (Tc17 cells). Non-MAIT, CD1d-independent CD161-expressing T-cells also exist and are characterized as generally effector memory cells with a stem cell like phenotype. Gene expression analysis of this enigmatic subset indicates a significant enhancement in the expression of cytotoxic granzyme molecules and innate like stress receptors in CD8+NK1.1+/ CD8+CD161+ cells in comparison to CD8+ cells that do not express NK1.1 or CD161. First identified and studied in the context of viral infection, the role of CD8+CD161+ T-cells, especially in the context of tumor immunology, is still poorly understood. In this review, the functional characteristics of the CD161-expressing CD8+ T cell subset with respect to gene expression profile, cytotoxicity, and tissue homing properties are discussed, and application of this subset to immune responses against infectious disease and cancer is considered.